Prevalence of MRSA ST398 Carriage in Nursing Home Residents in an Area of Spain With a High Density of Pig Farming. (5th December 2017) - Reynaga, Esteban; Torres, Carmen; Garcia-Nuñez, Marian; Navarro, Marian; Vilamala, Anna; Puigoriol, Emma; Enrico Lucchetti, Gianni; Nunes, Daniella; Silva, Adriana; Sabrià, Miquel
Abstract : MRSA nasal carriage was detected in 15.7% of 204 residents from 6 nursing homes (NHs) in the Osona region (Barcelona, Spain), and the MRSA-ST398 lineage was identified in 15.6% of MRSA-positive residents and in 2.5% of all NH residents evaluated. Most MRSA-ST398 carriers (4 of 5) had direct or indirect contact with pig farms. Infect Control Hosp Epidemiol 2018;39:90–93